Trial of Aspirin and RA 233 in Prevention of Post-operative Deep Vein Thrombosis - Wood, Edward H.; Prentice, Colin R.M.; McGrouther, D. Angus; Sinclair, John; McNicol, George P. (Thrombosis and Haemostasis, 1973)
Although the oral anticoagulants provide effective prophylaxis against postoperative deep vein thrombosis following fracture of neck of femur there is a need for an antithrombotic agent which needs less laboratory control and does not cause haemorrhagic complications. It has been suggested that drugs causing inhibition of platelet function may fulfil these requirements. A controlled trial was carried out in which aspirin, RA 233, or a combination of these drugs was compared with a placebo in the prevention of post-operative deep vein thrombosis. In thirty patients undergoing surgery for fractured neck of femur the incidence of post-operative calf vein thrombosis, as detected by 125I-fibrinogen scanning, was not significantly different between the untreated and treated groups.